(untitled) (Ciudades, 2017)
There are factors of the contemporary scene, as the rise of multi-media and interpersonal communication, which increase and complicate the proximity, definable as socius scale or density that would rule a state of community live together. There are also others, too recent, as the importance of otherness, reflected both in multiethnic settings new urbanity and the relative failure of urban theories of condensation of different social classes or social leyers decanted into different circumstances of insecurity or violence. These factors induce to consider the recent changes related to that urban proximity condition, that is linked to its raison d’être, perhaps according to their medieval zero degree.